The cumulation of intellectual property rights, with specific reference to the cumulation of patent and design rights - Milosavljević Nikola (Zbornik Radova Pravnog Fakulteta u Nišu)
In this paper, the author first explores the terminology and systematics in the field of cumulation of intellectual property rights, in an attempt to determine the meaning of certain terms and harmonize the terminology in this field, and then analyzes the reasons for the existence of overlapping terms and their permissibility. The conclusions drawn in this part are further used in the analysis of the relationship between the patent and industrial design rights. To this effect, the author first examines the similarities between these rights, by taking into account all overlapping aspects. Then, the author provides a detailed analysis of the differences between patent and industrial design rights. The general considerations and the provided analyses of similarities and differences have been used for further research on the possible overlapping between patent and industrial design rights. Based on the conducted research, the author concludes that there are insufficient arguments for a general prohibition of all these cumulations; thus, overlaps in each of these areas have to be regulated separately. Yet, in terms of the cumulation of patent and industrial design rights, the author has established that this overlap is relatively difficult to attain. Therefore, it currently does not pose an excessive risk for competition, but it does not exclude such a possibility in the future.